Oct4 Regulates the Transition of Cancer Stem-Like Cells to Tumor Endothelial-Like Cells in Human Liver Cancer - Liu, Hong-Lin; Tang, Hong-ting; Yang, Han-lin; Deng, Ting-Ting; Xu, Ya-Ping; Xu, Shi-Qing; Peng, Liang; Wang, Zai; Fang, Qing; Kuang, Xiao-Yan; Li, Qin-Shan (Frontiers in Cell and Developmental Biology, 2020)
Octamer-binding transcription factor 4 (Oct4) has been recently implicated as a proangiogenic regulator in several induced pluripotent stem cells (iPSCs), however, its role in cancer stem-like cells (CSCs) remain unclear. We report here that Oct4 participates in tumor vasculogenesis in liver CSCs (LCSCs). We identify that LCSCs possess the potential of endothelial trans-differentiation under endothelial induction, present endothelial specific markers and their functions in vitro, and participate in neovasculogenesis in vivo. The knockdown of the Oct4A by short hairpin RNA (shRNA) in LCSCs represses endothelial trans-differentiation potential, but induces endothelial lineage-restricted differentiation, the latter is positively regulated by Oct4B1. Furthermore, Oct4 regulates vasculogenesis in LCSCs may be via the AKT-NF-κB-p65 signaling pathway. This work reveals Oct4, which is a crucial regulator, plays a critical role in tumor endothelial-like cells transition of LCSCs through Oct4A and Oct4B1 by different ways. The simultaneous inhibition of both the isoforms of Oct4 is hence expected to help regress neovascularization derived from CSCs. Our findings may provide insights to the possible new mechanisms of tumor vasculogenesis for primary liver cancer.